Higher-order thinking skills among male and female students: An experimental study of the problem-based calculus learning model in secondary schools - Hasan Djidu; Jailani Jailani; Heri Retnawati (Beta: Jurnal Tadris Matematika, 2021)
[English]: This study aims to examine the effectiveness of the problem-based calculus learning model (PB-CLM) towards students’ higher-order thinking skills (HOTS). PB-CLM is a modification of problem-based learning’s (PBL) syntax. It was a quasi-experimental with a group pretest-posttest design involving 351 11th-grade students as the population. Seventy-one students of two classes were randomly selected as a sample. Data was collected through pretest and posttest developed from three aspects of HOTS; analysis, evaluation, and synthesis. To determine the effectiveness of PB-CLM, paired sample t-test and independent sample t-test with a significance level of 5% (α = 0.05) were used. The results show that students’ activities during the learning process in PB-CLM has a positive effect on increasing their HOTS (mean difference = 30.141; sig one-tailed = 0.000). Furthermore, there was no significant difference in HOTS among male and female students, both at the pretest and posttest (mean difference = 0.81731; sig.= 0.295). Likewise, the increase in HOTS scores (posttest-pretest) did not differ significantly between gender (mean difference = 0.88141; sig. one-tailed = 0.740). [Bahasa]: Penelitian ini bertujuan untuk menguji keefektifan problem-based calculus learning model (PB-CLM) terhadap higher-order thinking skills (HOTS) siswa. PB-CLM merupakan modifikasi dari sintaks model problem-based learning (PBL). Penelitian ini menggunakan rancangan quasi eksperimen dengan desain one group pretest-posttest yang melibatkan 351 siswa kelas XI sebagai populasi penelitian. Tujuah puluh satu siswa dari 2 kelas dipilih secara acak sebagai sampel. Data penelitian dikumpulkan dengan menggunakan pretest dan posttest yang dikembangkan dari 3 aspek HOTS; analisis, evaluasi, dan sintesis. Untuk mengetahui keefektifan PB-CLM digunakan paired sample t-test dan independent sample t-test dengan taraf signifikansi 5% (α = 0,05). Hasil analisis menunjukkan aktivitas siswa selama pembelajaran dengan PB-CLM efektif dalam meningkatkan HOTS (mean difference = 30,141; sig.one-tailed = 0,000). Lebih lanjut, tidak ditemukan perbedaan yang signifikan antara HOTS siswa laki-laki dan perempuan, baik pada pretest maupun posttest (mean difference = 0,81731; sig.= 0,295). Begitu pula peningkatan skor HOTS (posttest-pretest) juga tidak berbeda signifikan antara siswa laki-laki dan perempuan (mean difference = 0,88141; sig. one-tailed = 0,740).